Learning in leisure: stimulating outdoor learning through an Islamic ideology at Universiti Sains Islam Malaysia/ Mohammad Hafizi Abdul Mahadi - Abdul Mahadi, Mohammad Hafizi (2017)
Aim of this research is enhancing and improving the outdoor learning and identity of a campus as well as to create conducive campus outdoor environment through Islamic ideology that contribute of social spaces towards a sustainable and healthy design as well as to identify problems and issues relating to the planning and design of the campus in Malaysia. The issue that related into the outdoor learning space is the system of educational that more focus on indoor rather that outdoor. This research on the University sains islam Malaysia (USIM) that has the same issue of this particular study and the same time also has a big potential of outdoor learning development. As the outcome of study, the resulting analysis and synthesis of the study will have provided the design solution and recommendation of the site area that to become more live able campus and the same time implementing the outdoor learning as a one of the core area for the educational approach. Besides that, the result of the proposed design will generate the idea of injecting the Islamic ideology into the design to preserve and enhancing the Islamic identity of the campus.